Bouncing Back from Health Shocks: Locus of Control, Labor Supply, and Mortality - Stefanie Schurer (Institute for the Study of Labor (IZA), 2014)
Policy-makers worldwide are embarking on school programmes aimed at boosting students' resilience. One facet of resilience is a belief about cause and effect in life, locus of control. I test whether positive control beliefs work as a psychological buffer against health shocks in adulthood. To identify behavioural differences in labour supply, I focus on a selected group of full-time employed men of working age and similar health. Men with negative control beliefs, relative to men with positive beliefs, are 230-290% more likely to work part-time or drop out of the labour market after a health shock. In old age men with negative control beliefs are by a factor of 2.7 more likely to die after a health shock. The heterogeneous labour supply responses are also observed for other non-cognitive skills, but only for the ones which correlate with control beliefs. Interventions aimed at correcting inaccurate beliefs and negative perceptions may be a low-cost tool to moderate rising public expenditures on social protection and health care.
Keywords: I12; J24; 330; non-cognitive skills; locus of control; labor supply; mortality; health shocks; SOEP